Atmospheric Acetaldehyde: Importance of Air‐Sea Exchange and a Missing Source in the Remote Troposphere. Issue 10 (28th May 2019) - Wang, Siyuan; Hornbrook, Rebecca S.; Hills, Alan; Emmons, Louisa K.; Tilmes, Simone; Lamarque, Jean‐François; Jimenez, Jose L.; Campuzano‐Jost, Pedro; Nault, Benjamin A.; Crounse, John D.; Wennberg, Paul O.; Kim, Michelle; et al.
Abstract: We report airborne measurements of acetaldehyde (CH3 CHO) during the first and second deployments of the National Aeronautics and Space Administration Atmospheric Tomography Mission (ATom). The budget of CH3 CHO is examined using the Community Atmospheric Model with chemistry (CAM‐chem), with a newly developed online air‐sea exchange module. The upper limit of the global ocean net emission of CH3 CHO is estimated to be 34 Tg/a (42 Tg/a if considering bubble‐mediated transfer), and the ocean impacts on tropospheric CH3 CHO are mostly confined to the marine boundary layer. Our analysis suggests that there is an unaccounted CH3 CHO source in the remote troposphere and that organic aerosols can only provide a fraction of this missing source. We propose that peroxyacetic acid is an ideal indicator of the rapid CH3 CHO production in the remote troposphere. The higher‐than‐expected CH3 CHO measurements represent a missing sink of hydroxyl radicals (and halogen radical) in current chemistry‐climate models. Plain Language Summary: The Earth's atmosphere and its ability to self‐regulate and cleanse itself is dependent on a complex interplay of trace chemical species, some of which are emitted from the biosphere, while others are from human activities or fires. One of these key species, acetaldehyde, was measured as part of the recent Atmospheric Tomography Mission, an aircraft (National Aeronautics and Space Administration DC‐8) experiment transecting the lengths of the Pacific and Atlantic Oceans during two seasons, measuring greenhouse gases and chemically reactive gases and particles. These measurements allow us to test our ability to model the chemical state of the atmosphere. The results indicate that the ocean is a large source of acetaldehyde and the analysis here suggests additional mechanisms that narrow the gap between observations and simulations but also reveal that an additional unexplained source or sources remain(s) in the remote free troposphere. It is critical to understand this missing carbon source because it has significant implications for understanding the cycle of oxidants which, in turn, provide for the means of removing (cleaning) trace gases including methane, an important greenhouse gas, from the atmosphere. Key Points: Observed acetaldehyde (CH3 CHO) in the remote troposphere is compatible with observed peroxyacetic acid (PAA) within uncertainties We speculate that there is a missing CH3 CHO source in the remote atmosphere and observed organic aerosols cannot explain the observed CH3 CHO The ocean is a net source of CH3 CHO; the ocean biogeochemistry control on the atmospheric chemistry warrants further investigation